https://psyjournals.ru/en/psyedu/2020/n1/Pereverzeva_Braginets_Tyushkevic.shtml - Vasilyeva E.N; Scherbakov A.V (Moscow State University of Psychology and Education, 2020)
The article presents data of a study on gender differences of the personality component in the structure of career potential in future managers. Identifying the level of career potential components formation at the initial stage of university education allows to outline a program of harmonization of career potential and to implement it at each stage of university education, taking into account the age, personal characteristics and professional orientation of the students. The study involved 234 students aged 18-19 years, 117 males and 117 females. It was revealed that the male subjects, as compared to the female subjects, showed higher developmental levels of motivational, regulatory and emotional characteristics of the personality component in the structure of their career potential, which in the future could become the basis for their rapid career growth. The articleconcludes that there's an obvious need for the development and implementation of programmes supporting the individual career path in university students.